2021
DOI: 10.1107/s2059798321009025
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotein catalysis: structural and mechanistic insights into oxidoreductases from neutron protein crystallography

Abstract: Metalloproteins catalyze a range of reactions, with enhanced chemical functionality due to their metal cofactor. The reaction mechanisms of metalloproteins have been experimentally characterized by spectroscopy, macromolecular crystallography and cryo-electron microscopy. An important caveat in structural studies of metalloproteins remains the artefacts that can be introduced by radiation damage. Photoreduction, radiolysis and ionization deriving from the electromagnetic beam used to probe the structure compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 259 publications
(232 reference statements)
0
13
0
Order By: Relevance
“…36,37 Neutron protein crystallography is also a non-destructive technique ideally suited for the study of radiation-sensitive metalloproteins for characterization of catalytic intermediates. 38 The application of cryo-neutron protein crystallography to study the protonation states of activated oxygen catalytic intermediates has been demonstrated by Raven, Moody and coworkers for the characterization of compound I and compound II. 39,40 In particular, a neutron crystallography study of cytochrome c peroxidase (CcP) resulted in cryo-capture and characterization of a deprotonated Fe( iv )O compound I species in a 2.5 Å resolution structure.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Neutron protein crystallography is also a non-destructive technique ideally suited for the study of radiation-sensitive metalloproteins for characterization of catalytic intermediates. 38 The application of cryo-neutron protein crystallography to study the protonation states of activated oxygen catalytic intermediates has been demonstrated by Raven, Moody and coworkers for the characterization of compound I and compound II. 39,40 In particular, a neutron crystallography study of cytochrome c peroxidase (CcP) resulted in cryo-capture and characterization of a deprotonated Fe( iv )O compound I species in a 2.5 Å resolution structure.…”
Section: Introductionmentioning
confidence: 99%
“…This makes the structure determination of the native/resting state difficult. One way of circumventing photoreduction is to use neutrons instead of X-rays for crystallographic studies of metalloproteins (Schro ¨der & Meilleur, 2021), though this imposes severe limitations on the systems that can be studied, as much bigger crystals are required for neutron diffraction. Furthermore, reduction of transition metals by X-rays may be a convenient reaction trigger for studies of enzymatic reactions in crystals (Bourgeois & Weik, 2009;Bourgeois & Royant, 2005).…”
mentioning
confidence: 99%
“…Likewise, in the humans’ case, the conversion of D-Glucuronate to L-Gulonate occurs mainly through aldehyde reductase (GR) and to a smaller extent with aldose reductase’ (AR) contribution ( Figure 5 ) [ 51 , 65 , 66 ]. Considering that the common molecular mechanism of the body’s limited ability to synthesize vitamin C is the absence of GULO [ 68 , 69 , 70 , 71 ], genetically, it is considered that the loss of synthesizing the ascorbic acid is likely due to the complete loss of the L-gulono-γ-lactone oxidase (GULO) gene.…”
Section: Biochemistry Of Antioxidants and Their Mode Of Actionmentioning
confidence: 99%